A novel post-mortem pathogen discovery program detects an outbreak of Echovirus E7: Uganda, 2022–2023 - Sonja L. Weiss; Sonja L. Weiss; Nicholas Bbosa; Nicholas Bbosa; Nicholas Bbosa; Gregory S. Orf; Gregory S. Orf; Michael G. Berg; Michael G. Berg; Deogratius Ssemwanga; Deogratius Ssemwanga; Sam Kalungi; et al. (Frontiers in Microbiology)
ObjectivesUtilizing post-mortem examination for routine monitoring of infectious diseases and pandemic preparedness is a common-sense, yet uncommon, public health measure. Here, we established a novel mortuary surveillance program in Uganda that leverages the unbiased nature of metagenomic next-generation sequencing (mNGS) to detect pathogens in recently deceased individuals.MethodsBetween October 2022 and December 2023, specimens and patient metadata were collected from 2,607 individuals across five mortuary sites around Kampala. Specimens were pre-screened for hemorrhagic fever viruses by RT-qPCR and a subset (n = 134) of RT-qPCR negatives were sequenced by mNGS.ResultsA variety of DNA (herpes, parvovirus, bufavirus) and RNA (Saffold, Salivirus, HAV) viruses, vectored (Bartonella, Rickettsia) and nosocomial (Enterobacter, Klebsiella) bacterial infections, and potentially lethal respiratory pathogens (e.g., Cryptococcus neoformans, Corynebacterium diphtheria) were detected. A localized outbreak of Enterovirus B (EV-B), specifically a recombinant Echovirus E7, was observed in Kampala. An epidemiologic assessment indicated that most identified pathogens were acquired via direct and/or indirect contact (e.g., fecal-oral, fomites) and that other modes of transmission (e.g., food-borne, insect-vectored) played a less significant role.ConclusionIntegration of mortuary surveillance, coupled with mNGS, into public health systems represents a powerful strategy for identifying unrecognized outbreaks and monitoring the (re-) emergence of infectious diseases.